Effect of Workplace Noise on Hearing Ability in Tile and Ceramic Industry Workers in Iran: A 2-Year Follow-Up Study - Mehrdad Mostaghaci; Seyyed Jalil Mirmohammadi; Amir Houshang Mehrparvar; Maryam Bahaloo; Abolfazl Mollasadeghi; Mohammad Hossein Davari (The Scientific World Journal)
Introduction. Noise as a common physical hazard may lead to noise-induced hearing loss, an irreversible but preventable disorder. Annual audiometric evaluations help detect changes in hearing status before clinically significant hearing loss develops. This study was designed to track hearing threshold changes during 2-year follow-up among tile and ceramic workers. Methods. This follow-up study was conducted on 555 workers (totally 1110 ears). Subjects were divided into four groups according to the level of noise exposure. Hearing threshold in conventional audiometric frequencies was measured and standard threshold shift was calculated for each ear. Results. Hearing threshold was increased during 2 years of follow-up. Increased hearing threshold was most frequently observed at 4000, 6000, and 3000 Hz. Standard threshold shift was observed in 13 (2.34%), 49 (8.83%), 22 (3.96%), and 63 (11.35%) subjects in the first and second years of follow-up in the right and left ears, respectively. Conclusions. This study has documented a high incidence of noise-induced hearing loss in tile and ceramic workers that would put stress on the importance of using hearing protection devices.